Developing Learning Materials Through AI for Germany Class as a Foreign Language - Julaikah, Dwi Imroatu; Subandi, Subandi; Mustofa, Ali; Ridwan, Agus (Proceeding of International Joint Conference on UNESA, 2025)
Learning materials is one of the keys for teachers to conduct a teaching-learning process in the classroom well. The materials are one of components and the source for teachers to teach perfectly in the classroom. Using AI for teachers to create learning materials has a positive impact, such as increasing the effectiveness. But not all AI can be used by the German teachers in Indonesia. This Article aimed encouraging AI to develop teaching materials, especially AI which are rarely utilized the teacher in Indonesia. The article focuses on two discussions (1) How to develop learning materials through AI -Gemini for Germany Class? (2) How to develop learning materials through AI- Quizlet for Germany Class. The methods which used in this study are literature review and library research. Google Forms was also used for data collection in this study. It was obtained from 20 German teachers to know what kind of AI that they used. Research results showed that (1) Gemini can help in developing materials for Germany teacher such as making lesson plan, exercises for the student (2) Quizlet can also provide a lot of various learning materials for Germany class. In conclusion that using AI appropriately by teachers is important and enhancing teachers’ skills in using AI should be done to ensure the successful implementation of AI in German language teaching class.